Synthesis of unprotected and borane-protected cyclic phosphines using Ru- and Mo- based olefin metathesis catalysts. - Slinn, C; Redgrave, A; Hind, S; Edlin, C; Nolan, S; Gouverneur, V (2003)
Ru- and Mo-based catalysts can be used in ring closing metathesis (RCM) reactions to synthesise cyclic phosphines protected as their borane complexes. The compatibility of the Schrock Mo-catalyst and the N-heterocyclic carbene Ru-catalysts with this class of substrates is particularly noteworthy as asymmetric RCM (ARCM) is now emerging as a new tool for the preparation of homochiral phosphines. One of the key results is that the Mo-catalyst allows the ring closure of the unprotected diallylphenylphosphine with 95% conversion.